The development and initial validation of the Daily Experiences of Pleasure, Productivity and Restoration Profile - Atler, Karen E., author; Cobb, R. Brian, advisor; Wood, Wendy, advisor; Makela, Carole, committee member; Vaske, Jerry, committee member (Colorado State University. Libraries, 2012)
Occupational scientists and occupational therapists believe that people experience time and occupation differently, and that understanding these unique subjective experiences is essential to enhance the understanding of occupational participation, health and well-being. Yet the efforts toward the identification and development of ways of understanding people's unique subjective experiences are limited. In this dissertation, the researcher provides the theoretical underpinning of a newly developing instrument designed to capture the objective and subjective experiences of occupational engagement titled the Daily Experiences of Pleasure, Productivity and Restoration Profile (PPR Profile) (Atler, 2008) and reports the validity evidence of the PPR Profile as examined in two studies. Cognitive interviewing was used in the first study to examine validity evidence based on test content, response processes, and the consequences of completing the instrument. The study provides beginning validity evidence of the PPR Profile's use as an instrument designed to capture the subjective experiences of daily activities. In addition, the study illustrates the benefits of using cognitive interviewing as a means of engaging clients who may potentially use the instrument in the development process. In the second study, validity evidence related to consequential and convergent validity was examined using a mixed method design. Adults living with the consequences of stroke completed three health surveys and the PPR Profile for three days. Use of the PPR Profile increased awareness of daily activities and related experiences. Although there was limited convergent validity evidence gathered in the study, consequential validity evidence indicated that participants' completion of the PPR Profile led to reflection and examination. However awareness was not always seen by participants as beneficial. Potential reasons for the limited convergent validity found are discussed.
Keywords: occupation; restoration; productivity; instrument development; pleasure; subjective experience